Impact of climate change, biodiversity loss, and pollution on the incidence and manifestation of depressive and anxiety disorders - Karl, Sebastian; Brandt, Lasse; Luykx, Jurjen J.; Dom, Geert (Current opinion in psychiatry, 2025)
Purpose of review: Climate change, biodiversity loss, and pollution present a major threat to health. Although emphasis has been put on physical health impacts, evidence on the mental health consequences is now also accumulating quickly. Given the rapid developments in the field, this article provides an expert opinion on the emerging research. - Recent findings: Umbrella reviews are adding more high-level evidence on the associations of environmental crises and mental health. Individual studies are focusing on specific aspects of environmental crises and mental health, shedding light on potential direct links between climate change and mental health. Further studies are aiming to quantify individual burden and societal cost of the environmental crises and mental health nexus and to identify those most at risk for negative mental health outcomes. Many studies focus on eco-emotions, attempting to characterize them further, provide tools for quantification, and to determine their effect on functioning. - Summary: Although the accumulating research on the impacts of environmental change on depression and anxiety is filling important knowledge gaps, important questions remain, for example concerning the risk factors for the development of mental health disorders caused by ecological crises, tailored preventive strategies, and concerning the effects of biodiversity loss on mental health. Health systems need to further develop responses to these environmental crises.
Gesehen am 02.01.2026